Addition of κ-carrageenan increases the strength and chewiness of gelatin-based composite gel. (July 2022) - Cheng, Zihang; Zhang, Binjia; Qiao, Dongling; Yan, Xiaolong; Zhao, Siming; Jia, Caihua; Niu, Meng; Xu, Yan
Abstract: Although gelatin-based composite gels have been widely used in the food and pharmaceutical industries, further research is needed to improve gel strength. This work reported the microstructure and gel properties of gelatin-based composite gels containing different contents of κ-carrageenan (CGN) or konjac glucomannan (KGM). The rheological and textural results revealed that the gelling temperature, melting temperature, strength (from 1.68 to 4.13 times), toughness, and chewiness of the composite gel were positively correlated with the addition of CGN. The microscopy and infrared spectroscopy showed that gelatin and CGN molecules could be clustered in helices by electrostatic interactions and hydrogen bonding to form excellent gel networks with outstanding gelation properties. However, gelatin and KGM could either be compatible with or separated from each other. At a low KGM content, the gelatin-based composite gel was porous and had a dense gel structure. When the KGM content was 0.3%, the composite gel showed greater ordering degree. Thus, the addition of the proper amount of CGN to gelatin led to composite gels with better strength, toughness, and chewiness, whereas the addition of KGM generated gels being easy to chew and swallow. Graphical abstract: Image 1 Highlights: Addition of κ-carrageenan enhanced strength, toughness, and chewiness of gelatin-based gel. Addition of κ-carrageenan promoted gel formation and suppressed gel disruption. Phase separation occurred for gelatin-based gel with >0.3% konjac glucomannan.